Standardized catch and survival rates, and effect of a ban on shark retention, Palau pelagic longline fishery. Issue 6 (3rd November 2015) - Gilman, Eric; Chaloupka, Milani; Merrifield, Matt; Malsol, Nanette D.; Cook, Chuck
Abstract: Pelagic longline fisheries affect both market and vulnerable bycatch species and can have broad effects on community structure and processes. Observer data from the Palau longline fishery were analysed to identify opportunities to mitigate vulnerable species bycatch, determine temporal trends in local abundance, and assess changes following a ban on shark retention and wire leaders. Catch and haulback condition data for bigeye and yellowfin tunas, blue and silky sharks and pelagic stingrays were fitted to standardized catch and survival rate models. The fishery caught silky and blue sharks, olive ridley sea turtles and other species of conservation concern. Changing from shallow sets to deep daytime sets might reduce shark and sea turtle catch rates but increase turtle haulback mortality rates, maintain economically viable tuna catch rates, but increase catch rates of pelagic stingrays, a lower conservation concern than main caught species of sharks and turtles. Focusing fishing effort during the middle of the calendar year would maximize yellowfin tuna and minimize silky shark standardized catch rates, but maximize blue shark catch rates. A large decline in shark fishing mortality rate very likely occurred following a ban on shark retention and wire leaders. This was due to large reductions in the nominal shark catch rate and shark retention, partially offset by decreases in the shark haulback survival rate and pre‐catch survival rate. Significantly higher blue shark and lower pelagic stingray nominal catch rates occurred on wire vs. monofilament leaders. Significantly higher blue shark and lower yellowfin tuna nominal catch rates occurred on sets using shallow 'shark lines'. It is a research priority to compare the probability of shark pre‐catch survival after escaping from monofilament leaders with an ingested hook and trailing line to the survival probability when captured on wire leaders. Copyright © 2015 John Wiley & Sons, Ltd.